LES ENJEUX DE LA MAINTENANCE DES RÉSEAUX DES OPÉRATEURS DE TÉLÉPHONIE MOBILE ENTRE OPERATEURS, PRESTATAIRE ET SOUS-TRAITANT, CAS DE HUAWEI ET ELMS EN RDC - MONGAMBO, Ir. Dieudonné LIBENGE (IJRDO -Journal of Computer Science Engineering, 2023)
The maintenance system of the current mobile phone networks is dominated by the subcontracting that passes for one of the organizations that relaxes the client or the operator and allows it to focus more favorably on essential tasks of production, hear by commercial and marketing. Thus outsourcing is organized according to established criteria for reconciling cost and quality, it is used to make a selection initially for recruitment that can satisfy the specifications. In the DRC, the provider HUAWEI takes on a chance of dominance and treats with all the major mobile operators from the point of view maintenance and supplies of the equipment as it counts to its bosom several sub-portent, with whom it cooperates to organize a system of effective maintenance. To make its vision practice, strategically its subcontractors are geographically retapled in the maintenance zone. The ELMS subcontractor is renowned for the ex-region of Ecuador where Vodacom, Orange and Airtel are important. In this article we identify the continuous possibilities of maintenance structure in mobile and technical telephone networks aimed at reducing maintenance costs related to maintenance while optimizing the reliability of the networks. The objective principle of this article is developed a technical orientation and reference technical document at different levels for the maintenance of mobile phone equipment in the DRC by giving information on a judicious choice of maintenance partners, based on efficiencies of efficiency. Emergence of reliable networks in networks in the DRC.